2016
DOI: 10.21037/jtd.2016.03.67
|View full text |Cite
|
Sign up to set email alerts
|

Where do we go from here? Reappraising the data on anticoagulation in pulmonary arterial hypertension

Abstract: The use of anticoagulation as part of the treatment regimen in pulmonary arterial hypertension (PAH) remains a topic of debate. A recently published analysis of anticoagulation use in the Registry to Evaluate Early and Long-Term PAH Disease Management (REVEAL) study offers conflicting conclusions regarding the benefit of this therapeutic strategy. There remains no robust randomized trial in PAH weighing the risks versus benefits of including anticoagulation in treatment regimens, leaving clinicians to surmise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Since the use of anticoagulation in CTEPH is routine management, anticoagulation for SVA would not alter therapy; however, there is increasing recognition of the absence of benefit and potential for harm with anticoagulation in some forms of PAH 105 , 106 . This highlights the value of more carefully establishing the risks and benefits of anticoagulation for arrhythmia in PAH patients.…”
Section: Supraventricular Arrhythmiasmentioning
confidence: 99%
“…Since the use of anticoagulation in CTEPH is routine management, anticoagulation for SVA would not alter therapy; however, there is increasing recognition of the absence of benefit and potential for harm with anticoagulation in some forms of PAH 105 , 106 . This highlights the value of more carefully establishing the risks and benefits of anticoagulation for arrhythmia in PAH patients.…”
Section: Supraventricular Arrhythmiasmentioning
confidence: 99%
“…Given the uncertainty regarding the survival benefit in IPAH patients, as well as the concern for increased mortality in SSc-PAH exposed to systemic anticoagulation, the decision is currently left to the provider and patient on an individualized basis and the optimal strategy in drug-induced PAH patients is unknown. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Since then, a number of prospective and retrospective cohort studies, observational studies, and meta-analyses have revealed conflicting results on whether long-term anticoagulation improves mortality in PAH patients. 5 9 The controversy surrounding anticoagulation in PAH patients was recently highlighted by analyses from two large PAH registries. Data from the European-based Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension study showed a significant survival benefit in IPAH patients receiving anticoagulation while data from the U.S.-based Registry to Evaluate Early and Long-Term PAH Disease Management (REVEAL) cohort did not show a survival benefit for IPAH patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, a clinical trial studying the effects of high‐dose calcium channel blocker therapy in idiopathic PAH (IPAH) patients showed that the use of concurrent anticoagulant therapy with warfarin improved overall survival, although the effect was primarily apparent in the patients who did not respond to calcium channel blocker treatment 4 . Since then, a number of prospective and retrospective cohort studies, observational studies, and meta‐analyses have revealed conflicting results on whether long‐term anticoagulation improves mortality in PAH patients 5 9 . The controversy surrounding anticoagulation in PAH patients was recently highlighted by analyses from two large PAH registries.…”
Section: Introductionmentioning
confidence: 99%